Predictors Patterns Of Bacterial Urinary Tract Infections Among Febrile Children Under-Five Years Of Age At Kampala International University Teaching Hospital - Nakalema, Gloria; Ortiz, Yamile A.; Agwu, Ezera (Chemistry and Pharmacy, 2015)
An accurate and reliable diagnosis of UTI in children is critical because they are usually underdiagnosed or over-diagnosed especially in children under five years of age. Antimicrobial susceptibility results are key to effective intervention. This study was done to determine the predictors patterns of bacterial urinary tract infections among febrile children aged less than 5 years presenting at Kampala International University Teaching Hospital. A hospital-based cross-sectional study was conducted in entry points of the pediatric ward of KIU-TH between December 2020 and March 2021. The study enrolled a total of 350 children 2-59 months by consecutive enrolment. Urinalysis and urine culure was done, clinical and demographic data was collected using questionnaires and data analysed using SPSS version 27 with significance at 95% confidence interval. Factors that were independently predictive of a UTI were age less than 24 months (p 0.002), male children (p 0.010), undernutrition (p 0.012), diarrhea (p 0.032), vomiting (p 0.005). Children who were wiped back to front after defecation (p 0.021), diapers use (p 0.014). Among the laboratory urinalysis predictors, Children with nitrites and those with more than 5 white blood cells at urine microscopy were 17.875(p <0.001) and 6.505(p<0.001) times more likely to suffer from Urinary tract infection respectively
Keywords: Predictors pattern; bacterial; urinary tract and infections